Morphological Responses and Productivity of Indigofera (Indigofera zollingeriana) with Varied Fertilization in Limestone Post-mining Land - Harwanto, Harwanto; Karti, Panca Dewi Manu Hara; Suwardi, Suwardi; Abdullah, Luki (Department of Agronomy and Horticulture, IPB University, 2025)
Indigofera is a protein-rich plant source for ruminants, with potential for introduction to marginal lands, such as limestone post-mining areas, through integration with reclamation activities. This study aims to determine the response of varying levels of organic fertilizer and NPK on the morphology and productivity of Indigofera zollingeriana introduced to limestone post-mining. The study employed a randomized block design with a 3 × 4 factorial pattern and four replications. The first factor was organic fertilizer at the rates of 0, 5, and 10 tons.ha-1, and the second factor was NPK, 0, 50, 100, and 150 kg.ha-1. Indigofera was planted in a 3 x 4 m2 plot with a 1 m planting distance and harvested four times. The results showed that the combination of organic fertilizer with NPK affected (p<0.05) the morphology, biomass production, and nutrient profile. The combination of 10 tons.ha-1 of organic fertilizer and 100 kg.ha-1 NPK optimally produced plant with up to 217.64 cm height, 18.28 tons.ha-1 fresh production per harvest, 4.96 tons.ha-1 dry matter per harvest, 28.78% crude protein, and 72.47% total digestible nutrient. Biomass production decreased in the dry season (third harvest). Conclusively, the combination of 10 tons.ha-1 organic fertilizer and 100 kg.ha-1 NPK produced Indigofera plants with optimum plant height, biomass production, crude protein, and total digestible nutrients. Indigofera plants can be utilized as revegetation plants and as a source of green fodder on limestone post-mining land.